Recommendations for the safe transport and delivery of laboratory animals to research centres - DONTAS (I.A. ΔΟΝΤΑ), I. A; MARINOU (K.A. ΜΑΡΙΝΟΥ), K. A. (Journal of the Hellenic Veterinary Medical Society, 2017)
This paper reviews the current requirements for the transport and delivery of laboratory animals to research centres, in order to achieve an optimum level of their health and welfare. Transport conditions, delivery and reception of animals at the facility, their clinical examination by a veterinarian and management during the acclimatization period are considered to be of maximum importance for the preservation of their health and welfare status, as well as for the validity of experimental results. The current existing legislation and the recommendations issued by European and international organizations are presented, taking into account the fact that they are under continuous update according to new scientific evidence.